(untitled) (MAUSAM, 1982)
Four major rain bearing processes for tropical belt, viz. (i) Synoptic scale disturbances, (ii) breeze circulations, (iii) Orographic circulations and (iv) convection over homogeneous surface have been discussed. Synoptic patterns for summer & winter for Havana have been analysed monthwise based on 50 years normals which give the number of rain bearing patterns in wet and dry years. The results derived show that the large scale disturbances determine time variations of rainfall.